2022
DOI: 10.3390/jpm12010028
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Incidence of Stroke in Patients with Gout Using Benzbromarone

Abstract: Gout is strongly associated with the incidence of atherosclerotic events, including stroke and myocardial infarction. Considering the increased prevalence of stroke in the population with gout, the aim of this study was to evaluate the effects of benzbromarone, a uricosuric agent, on the incidence of stroke in the population with gout. We used data from the Taiwanese National Health Insurance Registration Database (NHIRD). The benzbromarone user cohort included 15,143 patients; each patient was age- and sex-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Probenecid and Benzpromarone act through inhibition of URAT1 and GLUT9. Recently, it was shown that the use of Benzpromarone can be associated with a lower risk of stroke in patients diagnosed with gout [ 87 ]. It should be mentioned that Benzpromarone is considered one of the four drugs linked to severe hepatotoxicity, and for this reason, it was withdrawn in the USA [ 88 ].…”
Section: Available Treatment Option For Lowering Uric Acidmentioning
confidence: 99%
“…Probenecid and Benzpromarone act through inhibition of URAT1 and GLUT9. Recently, it was shown that the use of Benzpromarone can be associated with a lower risk of stroke in patients diagnosed with gout [ 87 ]. It should be mentioned that Benzpromarone is considered one of the four drugs linked to severe hepatotoxicity, and for this reason, it was withdrawn in the USA [ 88 ].…”
Section: Available Treatment Option For Lowering Uric Acidmentioning
confidence: 99%
“…The reason for lower ischemic and hemorrhagic stroke incidence in the gout cohort in the first 3 years was unclear. Because the definition of gout in our study requires the use of a urate-lowering agent at enrolment, a previous study showed urate-lowering agents might reduce the incidence of stroke in gout patients [40]. Thus, the temporal lower incidence of stroke in the first 3 years may be because of the interference of urate-lowering agents.…”
Section: Discussionmentioning
confidence: 94%
“…168 Apart from that, benzbromarone significantly decreased the incidence of stroke and diabetes in gout patients aged 40 and above. 169,170 Even so, benzbromarone was never approved in the United States, and its withdrawal from the European market in 2003 was due to its adverse effects such as liver dysfunction and fulminant hepatitis. 171 PEGylated Recombinant Uricase.…”
Section: Urate-lowering Therapy (Ult)mentioning
confidence: 99%
“…Enomoto et al conducted a study on different uricosuric agents and reported that benzbromarone potently reduced urate reabsorption by 93% . Apart from that, benzbromarone significantly decreased the incidence of stroke and diabetes in gout patients aged 40 and above. , Even so, benzbromarone was never approved in the United States, and its withdrawal from the European market in 2003 was due to its adverse effects such as liver dysfunction and fulminant hepatitis …”
Section: Treatment Strategies For Goutmentioning
confidence: 99%